Reduced Apaf-1 levels in cardiomyocytes engage strict regulation of apoptosis by endogenous XIAP - Potts, Malia B. (The Rockefeller University Press, 2005)
Overexpression studies have identified X-linked inhibitor of apoptosis protein (XIAP) as a potent inhibitor of caspases. However, the exact function of endogenous XIAP in regulating mammalian apoptosis is less clear. Endogenous XIAP strictly regulates cytochrome c–dependent caspase activation in sympathetic neurons but not in many mitotic cells. We report that postmitotic cardiomyocytes, unlike fibroblasts, are remarkably resistant to cytosolic microinjection of cytochrome c. The cardiomyocyte resistance to cytochrome c is mediated by endogenous XIAP, as XIAP-deficient cardiomyocytes die rapidly with cytosolic cytochrome c alone. Importantly, we found that cardiomyocytes, like neurons, have markedly reduced Apaf-1 levels and that this decrease in Apaf-1 is directly linked to the tight regulation of caspase activation by XIAP. These data identify an important function of XIAP in cardiomyocytes and point to a striking similarity in the regulation of apoptosis in postmitotic cells.